Self-medication with antibiotics in the ambulatory care setting within the Euro-Mediterranean region; results from the ARMed project - Elizabeth Anne Scicluna; Michael A. Borg; Deniz Gür; Ossama Rasslan; Ibrahim Taher; Saida Ben Redjeb; Ziad Elnassar; Despo Pieridou Bagatzouni; Ziad Daoud (Elsevier, 2009)
Summary: Anecdotal data from the southern and eastern Mediterranean region suggests that self-medication with antibiotics is commonly practiced in many countries. In order to provide proper information on the situation, we undertook short structured interviews in out-patients clinics or primary health centres in Cyprus, Egypt, Jordan, Lebanon, Libya, Tunisia and Turkey. A total of 2109 interviews were undertaken of which 1705 completed the full questionnaire. Self-medication was reported by 19.1% (<0.1% in Cyprus to 37% in Lebanon) of respondents. Intended self-medication ranged from 1.3% (95% CI 0%, 3%) in Cyprus to 70.7% (95% CI 64%, 77%) in Jordan. Upper respiratory tract symptoms were the most frequent reasons for which respondents indicated they would self-medicate. 48.4% of the whole group replied that they kept antibiotics at home, being highest in Lebanon (60%, 95% CI 51%, 69%). We found a significant association between antibiotic hoarders and intended users of antibiotics for self-medication. Our data confirms that non-prescribed antibiotic use is high within ambulatory care in southern and eastern Mediterranean countries, being almost twice that reported in a similar European study. Corrective efforts are clearly required in the region to ensure proper use of antimicrobials so as to reduce pressure for antimicrobial resistance. Keywords: Self-medication, Antibiotics, Over-the-counter, Mediterranean, ARMed